Solomon's crown : a novel - Siegel, Natasha (Dell, 2023)
"Two destined rivals fall desperately in love-but the fate of medieval Europe hangs in the balance. 'A pair of thrones between us, and my heart clutched like a rosary within his hands . . .' Twelfth-century Europe. Newly-crowned King Philip of France is determined to restore his nation to its former empire and bring glory to his name. But when his greatest enemy, King Henry of England, threatens to end his reign before it can even begin, Philip is forced to make a precarious alliance with Henry's volatile son--risking both his throne, and his heart. Richard, Duke of Aquitaine, never thought he would be King. But when an unexpected tragedy makes him heir to England, he finally has an opportunity to overthrow the father he despises. At first, Philip is a useful tool in his quest for vengeance . . . until passion and politics collide, and Richard begins to question whether the crown is worth the cost. When Philip and Richard find themselves staring down an impending war, they must choose between their desire for one another and their grand ambitions. Will their love prevail, if it calls to them from across the battlefield? Teeming with royal intrigue and betrayal, this epic romance reimagines two real-life kings ensnared by an impossible choice: Follow their hearts, or earn their place in history"--